2016
DOI: 10.1055/s-0036-1571319
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-1 Levels in Term Newborns with Hypoxic–Ischemic Encephalopathy

Abstract: Objective This study aims to evaluate the correlation of changes in serum insulin-like growth factor-1 (IGF-1) levels with the clinical staging of hypoxic-ischemic encephalopathy (HIE) in term newborns. Study Design A prospective study of 29 newborns with HIE (stage I = 15, stage II + III = 14) and 28 healthy term newborns as the control group was performed in the neonatal intensive care unit. IGF-1 levels were obtained within 6 hours after birth from HIE and control groups and again on day 3 from HIE group. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The former pathway is induced early after infection where NF- κβ dissociates from its inhibitory protein (I κβ ) and translocates to the nucleus [ 28 30 , 106 ]. The noncanonical NF- κβ pathway involves lymphopoiesis and differentiation of immune cells [ 106 , 107 ] that seems to be in accordance with the recruits of T cells speculated precisely around the microvasculatures of the amygdala in the present work. Accordingly, chronic toxoplasmosis seems to be vitally regulated by the TNF- α /NF- κβ pathway.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The former pathway is induced early after infection where NF- κβ dissociates from its inhibitory protein (I κβ ) and translocates to the nucleus [ 28 30 , 106 ]. The noncanonical NF- κβ pathway involves lymphopoiesis and differentiation of immune cells [ 106 , 107 ] that seems to be in accordance with the recruits of T cells speculated precisely around the microvasculatures of the amygdala in the present work. Accordingly, chronic toxoplasmosis seems to be vitally regulated by the TNF- α /NF- κβ pathway.…”
Section: Discussionsupporting
confidence: 85%
“…Existence of the cyst-forming ME-49 T. gondii strain of the parasite was associated with IGF-1R hypoexpression in the cerebral cells especially in the amygdala. However, these low expressive patterns deprive the host cell-parasite microenvironment from (1) the modulatory and antifibrotic effects of the IGF-1 [ 105 ], (2) the protective role of IGF-1 against the inflammatory oxidative damage [ 106 ] and the hypoxic and ischemic insults [ 107 ], (3) the regeneration of the brain cells [ 60 ], (4) the normal glucose metabolism [ 58 , 59 ], (5) the protection against alterations in the hormonal axis of the hypothalamus-pituitary-adrenal gland and the circulating cortisol/dehydroepiandrosterone sulfate ratios [ 108 ], and (6) the guard against atherogenicity of the blood vessels [ 109 ]. Accordingly, this might explain the observed incidence of dementia with toxoplasmosis in prior studies [ 6 , 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the neonatal period coincidences with the most active processes of gliogenesis, oligodendrocyte survival and differentiation, as well as myelination of the newly derived neurons, the insufficient amounts of endogenous trophic factors, including IGF-1, might unfortunately efficiently contribute to the resulting myelin deficiency, or/ and malformation of the white matter tracts [56][57][58][59]. The recent clinical studies confirmed that the IGF-1 level in serum is significantly decreased in newborns with hypoxic-ischemic encephalopathy [60]. A number of preclinical studies have been performed based on IGF-1 systemic administration in order to at least partially alleviate deleterious effects of the experienced birth asphyxia.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective clinical study of newborns found that compared with the control group, the level of IGF‐1 was measured within 6 hours after birth, or the level of IGF‐1 was measured again on the 3rd day in the hypoxic‐ischemic encephalopathy (HIE) group and the control group. The results showed that the level of serum IGF‐1 in the hypoxic ischemic encephalopathy group was significantly lower than that in the control group (Umran RM, et al, 2016). These are the changes of IGF‐1 after neonatal cerebral ischemia and the decrease of IGF‐1 after adult cerebral ischemia.…”
Section: Changes Of Igf‐1 Expression After Cerebral Ischemiamentioning
confidence: 98%